Hubungan Self-Efficacy, Lama Menjalani Hemodialisis dengan Kualitas Hidup dan Self-Management pada Pasien Hemodialisis di Rumah Sakit Islam Sultan Agung Semarang - Anjalika Ulfarani; Retno Setyawati; Erna Melastuti (Journal of Health, Medical, and Psychological Studies, 2026)
Background: Hemodialysis is a long-term renal replacement therapy that often causes physical and psychological changes in patients. Self-efficacy and duration of hemodialysis play an important role in patients' ability to adapt, which affects their quality of life and self-management. This study aims to determine the relationship between self-efficacy and duration of hemodialysis with quality of life and self-management in hemodialysis patients at Sultan Agung Islamic Hospital in Semarang. Method: This study is a quantitative study using a cross-sectional approach. There were 105 respondents using total sampling technique. Data collection in this study used questionnaires which were then analyzed using Somers' d test. Results: The results of the study show a significant relationship between self-efficacy and quality of life (ρ=0,001< 0,05) as well as self-efficacy and self-management (ρ=0,001< 0,05). In addition, there was a significant relationship between the duration of hemodialysis and quality of life (ρ=0,001< 0,05) and the duration of hemodialysis and self-management (ρ=0,001< 0,05). Conclusion: There is a significant relationship between self-efficacy, duration of hemodialysis, quality of life, and self-management in hemodialysis patients at Sultan Agung Islamic Hospital in Semarang.